Teaching the violent past : history education and reconciliation - Cole, Elizabeth A. (Rowman & Littlefield Publishers : In cooperation with the Carnegie Council for Ethics in International Affairs, 2007)
During an armed conflict or period of gross human rights violations, the first priority is a cessation of violence. For the cease-fire to be more than a lull in hostilities and atrocities, however, it must be accompanied by a plan for political transition and social reconstruction. Essential to this long-term reconciliation process is education reform that teaches future generations information repressed under dictatorial regimes and offers new representations of former enemies. In Teaching the Violent Past, Cole has gathered nine case studies exploring the use of history education to promote.
Keywords: Peace -- Study and teaching -- Case studies.; Conflict management -- Case studies.; Paix -- Étude et enseignement -- Études de cas.; Gestion des conflits -- Études de cas.; SOCIAL SCIENCE -- General.; Conflict management; Peace -- Study and teaching; Geschichtsunterricht; Friedenserziehung; Konflikt -- Motiv; Versöhnung; Konflikt (Motiv); Case studies; Case studies.; Études de cas.